The relationship of board diversity and stock performance in monistic and dualistic board structures: Results from Germany and UK - Tim Alexander Herberger; Andreas Oehler (Journal of Corporate Accounting & Finance, 2023)
The analysis of the relationship between board diversity and corporate performance is a well-documented area of research. Our analysis of the stock market in Germany and the United Kingdom (UK) from 2005 to 2018 contributes to the literature by considering different corporate constitutions (monistic and dualistic) as well as a variety of diversity factors and diversity potential factors in a uniform analytical framework. We implement the stock price performance as a company performance proxy because this can be observed more easily by non-professional investors than Tobin's Q, commonly used in former studies, and represents a pure market-based view of the company performance. Based on generalized least squares panel regressions (GLS), our results reveal no significant difference between monistic and dualistic corporate constitutions regarding a possible relationship between diversity and company performance. They support former studies that the size of a top management board is significantly negatively related to company performance in the long run. Furthermore, no significant correlation can be found between changes in a board in a fiscal year and company performance, which was analyzed for the first time in such a framework.
Keywords: 650; corporate governance and control; diversity; financial performance